THE EFFECT OF SALES GROWTH AND OPERATING CAPACITY ON FINANCIAL DISTRESS (ON COSMETIC COMPANIES LISTED ON THE IDX IN THE PERIOD 2019-2023) - Sari, Diah Novita (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to analyze the effect of sales growth and operating capacity on financial distress in cosmetic companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. This study also compares the financial condition of companies before and after the COVID-19 pandemic using the Altman Z-Score method to measure the potential for bankruptcy. The results of the study indicate that sales growth has a negative effect on the company's financial condition, while operating capacity as an indicator of asset utilization efficiency also contributes to the risk of financial distress. Comparison of the Altman Z-Score before and after the COVID-19 pandemic revealed no significant differences, where the pandemic worsened the financial condition of most cosmetic companies due to decreased income and changes in people's consumption patterns.